Scaling the Center for Mechanized Agriculture business model - Guindo, Samuel; Dossou-Yovo, E. R (2024)
This report highlights the scaling-up efforts of the Center for Mechanized Agriculture (CEMA) business model in Mali, a collaborative initiative led by the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) project in partnership with the Syngenta Foundation for Sustainable Agriculture, and AfricaRice. It outlines the innovative integration of mechanized services with climate-smart agriculture (CSA) technologies to enhance productivity and resilience in rice-based systems. Key achievements in 2024 include establishing and supporting 12 CEMAs, training 129 young service providers, and delivering mechanized services to over 18,000 farmers, including nearly 8,000 women. The report also documents financial outcomes, with the revenues of the CEMAs exceeding $480,000. This partnership-based model demonstrates the potential of CEMA to transform agricultural practices in Mali, contributing to food security, rural livelihoods, climate resilience, and jobs creation to women and youth.